2016
DOI: 10.3934/ipi.2016019
|View full text |Cite
|
Sign up to set email alerts
|

Lavrentiev's regularization method in Hilbert spaces revisited

Abstract: In this paper, we deal with nonlinear ill-posed problems involving monotone operators and consider Lavrentiev's regularization method. This approach, in contrast to Tikhonov's regularization method, does not make use of the adjoint of the derivative. There are plenty of qualitative and quantitative convergence results in the literature, both in Hilbert and Banach spaces. Our aim here is mainly to contribute to convergence rates results in Hilbert spaces based on some types of error estimates derived under vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Hofmann, Kaltenbacher, and Resmerita [8] studied Lavrentiev regularization under variational source conditions. These authors did not explicitly focus on the bias, instead they showed the convergence rate for the overall regularization error.…”
Section: Known Results For Lavrentiev Regularization Under Adjoint Somentioning
confidence: 99%
See 2 more Smart Citations
“…Hofmann, Kaltenbacher, and Resmerita [8] studied Lavrentiev regularization under variational source conditions. These authors did not explicitly focus on the bias, instead they showed the convergence rate for the overall regularization error.…”
Section: Known Results For Lavrentiev Regularization Under Adjoint Somentioning
confidence: 99%
“…The authors in [1] and [8] prove convergence results u − u δ γ → 0 as δ → 0, both for a priori and a posteriori parameter choices, under the additional assumption that the solution u of (1) is a minimum-norm solution. For elements u which satisfy a source condition, either direct or adjoint, this automatically holds true, because u is in the orthogonal complement of the nullspace N (A).…”
Section: Tight Upper Bounds Under Adjoint Source Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…First our focus is on the Lavrentiev regularization approach based on formula (2.13), in which κ(j δ , g δ ) ∈ L 2 (Ω). The general theory of linear Lavrentiev regularization (see, e.g., [43] and also [2,12,24,36,37]) yields convergence and convergence rates results for the error of regularized solutions f ρ,δ with respect to the uniquely determined f * -minimizing solution f † to problem (IP −M N ). Taking into account that Lemma 2.2 holds, we immediately derive (see, e.g., [12,Rem.…”
Section: Lavrentiev Regularization Versus Tikhonov Regularization Formentioning
confidence: 99%
“…Due to formula (1.18), the Tikhonov regularization approach under consideration with specific misfit term also appears as a variant of the Lavrentiev regularization (see, e.g., [2,12,24,43]). After some operatortheoretic settings and preliminary results in Section 2, concerning also the ill-posedness of the linear inverse problem under consideration, we apply in Section 3 the general theory of classical Tikhonov and Lavrentiev regularization for such problems yielding propositions on convergence and convergence rates for the regularized solutions in the infinite dimensional Hilbert spaces.…”
Section: Introductionmentioning
confidence: 99%